Enhanced Interferon-β Response Contributes to Eosinophilic Chronic Rhinosinusitis - Jang, Yong Ju; Lim, Ji Youn; Kim, Seoyeon; Lee, Yoo La; Kweon, Mi-Na; Kim, Ji Heui (Frontiers in Immunology, 2018)
Type I interferon (IFN-I, including IFN-α and IFN-β) response has been implicated in eosinophilic inflammation, in addition to antiviral function. This study aimed to investigate the role of IFN-I in the pathogenesis of eosinophilic chronic rhinosinusitis (ECRS). IFN-α, IFN-β, cytokine expression, and IFN-β cellular localization in the NP tissue from control subjects and ECRS patients with nasal polyps (NP) were determined using real time-PCR, ELISA, and immunohistochemistry. ECRS was induced in wild-type (WT) and IFNAR1 knockout (Ifnar1-/-) mice by intranasal challenge with Aspergillus protease and ovalbumin. Stromal cells cultured from NP tissue were stimulated by exogenous IFN-β, and their CCL11 production and IRF3, IRF7, STAT1, STAT2, and IRF9 gene and/or protein expression were measured. IFN-β, IL-5, IL-13, and CCL11 expression was higher in the NP tissue from ECRS patients, compared to the control group. IFN-β was highly colocalized with the CD11c+ cells in NP. IFN-β levels positively correlated with IL-5, IL-13, and CCL11 levels as well as the number of eoisnophils in the sinonasal tissue and CT score. The histological severity of ECRS, levels of IL-4, IL-5, IL-13, and CCL11 in the nasal lavage fluid, and total serum IgE levels were less in Ifnar1-/- mice than in WT mice. CCL11 production, and STAT1 and STAT2 mRNA and STAT1, phospho-STAT1, and phospho-STAT2 protein expression were significantly increased by exogenous IFN-β in NP stromal cells. Our data suggest that IFN-β response was upregulated in ECRS and may play role in ECRS development. IFN-β may contribute to ECRS by enhancing CCL11 production. Thus, increased IFN-β response in the sinonasal mucosa may underlie ECRS pathogenesis.